Assessment of Effect of Perceived Social Support on School Readiness, Mental Wellbeing, and Self-Esteem: Mediating Role of Psychological Resilience - Shi, Yefei (Frontiers in Psychology, 2022)
Objective of this study is to investigate the impact of perceived social support on the self-esteem, mental wellbeing, and school readiness of left-behind (LB) children. It further aims at understanding the mediating role of psychological resilience between the relationships of perceived social support and self-esteem, mental wellbeing, and school readiness. For this purpose, population frame of the LB children between the ages of 8–12 years in Mainland China was taken. The sample size of 335 was taken to reach the findings through partial least square (PLS) structural equation modeling. The SmartPLS has been used to analyze the data. The results obtained in this study have shown that the perceived social support plays a very significant role in enhancing the mental wellbeing, self-esteem, and school readiness of the LB children. It has also been found that the perceived social support plays a positive role in the psychological resilience. Furthermore, it has also been found that the psychological resilience is an important predictor of self-esteem and school readiness. Further, the psychological resilience has proved to be significant mediator between the relationship of the perceived social support and self-esteem; and also between the relationship of the perceived social support and school readiness.